PROFIL PENGETAHUAN PENDUDUK TERHADAP OBAT GENERIK, MEREK DAN PATEN - Rissa, Mexsi Mutia; Puspita, Nabila Ayu (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Republic of Indonesia Law Number 36 of 2009 states that medicine is a combination of ingredients, including biological products that are used to affect or investigate physiological systems or pathological conditions in the framework of establishing a diagnosis, prevention, cure, recovery, health promotion and contraception for humans. Generic drugs are drugs whose patents have expired, so all pharmaceutical companies can produce them without the need to pay for patents. Branded drugs are drugs that are marketed under certain trade names registered by the manufacturer. Patented drugs are drugs that have just been produced and marketed by a pharmaceutical company that has had patents for 20 years. The purpose of this study was to determine the profile of the population's knowledge of generic drugs, branded drugs, and patent drugs. The descriptive observational research method by collecting primary data through questionnaires. The results of the study showed that 45 respondents (64.70%) had enough knowledge and 25 respondents (35.70%) had less knowledge. This shows that the profile of the population's knowledge of generic drugs, branded drugs, and patent drugs is considered quite good. The conclusion of this study is that the population's knowledge profile of generic drugs, branded drugs, and patented drugs is included in the sufficient category, namely 64.70%.